APLIKASI TEKNOLOGI FOOTWORK TRAINING UNTUK PENINGKATAN AGILITY PEMAIN FUTSAL SMAS AL HASANIYAH NW JENGGIK - Subakti Subakti; Lalu Hulfian (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2019)
Footwork exercises use many methods and methods of using games, cones etc. However, this method includes conventional methods and athletes are bored with the same method. Therefore, new methods are needed so that athletes get a new motivation and new enthusiasm to practice footwork. One form of footwork exercise that needs to be tried is technology using training. The technology used is a light mounted on a corner of the field and controlled by a remote control. The objectives to be achieved in this study are to study the effectiveness of the application of footwork training on the agility of futsal players. This type of research is research by applying the pretest and posttest to the subject that discusses the agility test using the agilty test. The population in this study were 14 futsal players at Al Hasaniyah NW Jenggik High School. Because the population is small, all populations are sampled and the sampling technique used is population studies. The technique of collecting data in this study uses documentation and tests to measure agility. Data analysis techniques using a different test means with the help of SPSS 17.0. The data collected and processed are the results of the measurement of the agility of futsal players of Al Hasaniyah NW Jenggik High School. This agility test uses the Side Step Test before practice (Pretest) and after practice (post test). Based on the results of the research and discussion explained in the previous chapter, it can be concluded that the conclusions in this study are as follows (1) It is necessary to increase the agility of Al Hasaniyah NW Jenggik High School Futsal Players from the application of Footwork Training Technology Applications. (2) Increased players increase 4.05% increase.